LRS Bianchi Type-I String Cosmological Models in fQ Gravity - Mukesh Kumar; Manvinder Singh; Mohit Bajaj; Hossam Kotb; Djeudjo Temene Hermann (Journal of Mathematics, 2023)
In the current study, we studied a fQ-gravitational, anisotropic, locally rotationally symmetric (LRS), Bianchi type-I spacetime universe. We have adopted the freely chosen function fQ=Q+αQ, where α is a model-free parameter. We assumed that the universe is filled with dusty string fluid and that the shear scalar (σ) and the expansion scalar (θ) are proportional to each other in order to solve field equations for the average Hubble parameter (H). The resultant Hubble function has been fitted with observational datasets Hz and SNe Ia datasets of apparent magnitude mz in order to obtain the best fit values for the cosmological parameters. Utilizing these best fit values throughout the analysis, many cosmic phenomena are examined. We have investigated cosmographic coefficients such as H,q,j,and s to see if an accelerated transit phase dark energy model of the cosmos exists. Also, we have classified the dark energy models that are explored using Om diagnostic analysis; our universe model is a quintessential dark energy model. The age of the universe as it exists right now has been roughly calculated by the model.